2005
DOI: 10.1080/00365590500386734
|View full text |Cite
|
Sign up to set email alerts
|

Is there any relationship between serum levels of interleukin-10 and atherosclerosis in hemodialysis patients?

Abstract: Patients with AS undergoing HD had low serum levels of the anti-inflammatory cytokine IL-10 and high serum levels of hs-CRP. These results may suggest that limitation of the anti-inflammatory response in atherosclerotic uremic patients is a triggering or contributory factor for AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Seyrek et al found low serum levels of IL-10 and high levels of high-sensitivity CRP in patients with atherosclerosis undergoing HD. They suggested that limitation of anti-inflammatory response in atherosclerotic uremic patients may be a triggering or contributory factor for atherosclerosis (22). Hyperhomocysteinemia in patients with CRF may accelerate oxidative stress, and lipid peroxidation may be involved in the occurrence of microinflammation state.…”
Section: Discussionmentioning
confidence: 97%
“…Seyrek et al found low serum levels of IL-10 and high levels of high-sensitivity CRP in patients with atherosclerosis undergoing HD. They suggested that limitation of anti-inflammatory response in atherosclerotic uremic patients may be a triggering or contributory factor for atherosclerosis (22). Hyperhomocysteinemia in patients with CRF may accelerate oxidative stress, and lipid peroxidation may be involved in the occurrence of microinflammation state.…”
Section: Discussionmentioning
confidence: 97%
“…40,41 On the other hand, decreased levels of IL-10 have been described in MHD patients with carotid atherosclerotic plaques. 42 Furthermore, a genotype associated with lower IL-10 production predicts cardiovascular death in MHD patients. 43 These data support the hypothesis that ARBs may be preferable to ACE inhibitors in limiting cardiovascular events in MHD patients.…”
Section: Discussionmentioning
confidence: 99%
“…33,62,63 Plasma levels of IL-10, one of the most important anti-inflammatory immune-regulating cytokines, 64 are usually elevated in CKD because of persistent underlying inflammation. 44,56,58 Hemodialysis patients with lower plasma IL-10 levels seem to be at greater risk for atherosclerosis, 65 whereas those patients genetically predisposed to produce higher IL-10 levels show better immune balance 66 and are at lower risk of cardiovascular events. 67 It can be argued that the balance between IL-6 and IL-10 is a more valid parameter to draw conclusions about the overall inflammatory status.…”
Section: Effects Of Regular Exercisementioning
confidence: 99%